Droga Polski do Unii Gospodarczej i Walutowej - perspektywy, szanse i zagrożenia - Ringhut, Eric; Gerlach, Philipp (Poland's Way to EMU - Prospects, Risks and Chances, 2005)
This paper deals with the question of what currency regime Poland should choose in the eve of EMU membership. This question seems to be highly important and on a top rank on agendas of international monetary economists because of the characteristics of CEECs, the recent break down of a currency board system (a hard peg that many countries apply) in Argentina and the clear future perspective of becoming EMU member. Especially the latter is interesting as Poland started transforming with a hard peg, moved towards a free float and will finally join a monetary union. Although this paper concentrates on Poland, it is interesting to note that the variety of currency regimes among the applicant countries is quite large. This heterogeneity is somewhat peculiar since all countries negotiate with the EU, undertake most of their international trade with the EU countries and share the same future perspective. Nevertheless, there are. differences in those countries that justify different currency regimes. Our focus will be on Poland and we try to lay down the pros and cons of two options for Poland. We first briefly describe the transition from an EU-candidate to a full member of the EU and EMU. We then highlight the most important economic indicators for the choice of the currency regime in section 3. In section 4 we go into detail about a free float which we assume to be a close proxy of a managed float for a theoretical discussion. A managed float is compatible whit ERM II and simultaneously represents one corner of the spectrum of possible regime for EMU applicants. One the other hand we analyse a curreny board system as well as a unilateral euroization as the other corner of the spectrum. Especially the latter gained enormous interest within the last 10 years. We finally try to recommend a particular regime on the basis of Poland's current economic condition and perspective that is able to ensure stability, maintain competitiveness, promote structural reforms and help to meet the Maastricht criteria. Section 5 summarizes our findings.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 62-93